Performance Investigation of Flat Plate Solar Collector using vegetable oil-based nanofluids - Wan Basiron, Wan Amirul Asyraf (IRC, 2020)
This project will illustrate the practicality of vegetable oil-based (Soybean oil) nanofluid with few nanoparticles including the single-type nanoparticles (Cu), oxide nanoparticles (CuO) and hybrid nanoparticles (Cu-Zn) on the performance of flat plate solar collector as an alternative for conventional working fluid. A numerical study of the vegetable oil-based nanofluid as the working fluid is conducted to visualize the temperature distributions and the efficiency of the flat plate solar collector by using specific formula. The thermophysical properties value of the nanoparticles is obtained from the classical model formula as there are lack of research paper that use vegetable oil as the based nanofluid in the experimental work. Finally, the project concluded that vegetable oil-based nanofluid is feasible as the alternative of the conventional fluid which water that has poor freezing point.